Pengaruh Rasio Keuangan terhadap Harga Saham Perusahaan yang Terdaftar di IDX30 - Afan Rahmat Hidayat; M.Taufiq (CV. Ulil Albab Corp, 2022)
In realizing economic development, it is inseparable from competitive business world competition so as to encourage economic activity from production, distribution to consumption and make companies need additional capital for expansion through initial public offerings, the creation of investment activities in the form of shares. However, in making investment decisions, it requires a fundamental analysis such as looking at financial statements and some financial ratios to maximize profits in the future. Thisresearch aims to analyzethe effect of the financial ratio on the share price of companies listed on idx30. The data needed, secondary data, namely financial statements and financial ratios during 2016 -2018 through Bursa Efek Indonesia, Yahoo Finance, Rti Business and Aapplication of stock investment Ajaib Sekuritas. Metode of this study, using multiple linear regression analysis such as Normality Test, Multicollinearity Test, Heteroskedasticity Test, F Test and T test through the help ofspss data processing program version 25.0. The results of this study are Earning per share (EPS), Price earning ratio (PER), Price book value (PBV) have a significant effect on the share price of companies listed on IDX30.